2020
DOI: 10.7759/cureus.11195
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction and Clinical Efficacy of Novel Blood Glucose Meters Featuring Color Range Indicators in Patients With Type 2 Diabetes: A Prospective Study

Abstract: Introduction Self-monitoring of blood glucose (SMBG) plays an important role in diabetes management. The Contour ® Next One glucometer is a recent glucometer that delivers blood glucose results by an immediate color indicator to aware users when blood glucose is at a critical high or low. The main purpose of the study was to assess the impact of an application of a blood glucose meter (BGM) having a color range indicator on clinical characteristics and glucose monitoring satisfaction (GMS) among patients havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A recent randomized controlled study [26] found that the usage of BGMs with Colour Range Indicator (CRI) reduces glycated haemoglobin (HbA1C)-HbA1C is a gold standard blood test for patients with diabetes that measures the proportion of glycated haemoglobin which is in correlation with the blood glucose level over the past 3 months. Other studies proved that the use of CRI improves the management of diabetes [20,22,23,25].…”
Section: Findings From the Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent randomized controlled study [26] found that the usage of BGMs with Colour Range Indicator (CRI) reduces glycated haemoglobin (HbA1C)-HbA1C is a gold standard blood test for patients with diabetes that measures the proportion of glycated haemoglobin which is in correlation with the blood glucose level over the past 3 months. Other studies proved that the use of CRI improves the management of diabetes [20,22,23,25].…”
Section: Findings From the Literature Reviewmentioning
confidence: 97%
“…By using a colour scale, patients can better interpret results, classify BG readings as low, high or in range, and make decisions accordingly [19]. The colour scale allows the definition of a glucose result as either "near low" or "near high" by glancing in the direction of below or above range segments, allowing patients to either take action before their score would become too high/too low or reflect on the reasons that generated "near low"/"near high" results [22,23]. The introduction of the colour system improves patients' feeling of being safe and in control because they are alerted when results are near high/low values [22,24,25].…”
Section: Findings From the Literature Reviewmentioning
confidence: 99%
“…At the time of the baseline visit and 12 weeks of the study, a trained interviewer introduced Glucose Monitoring Satisfaction Survey (GMSS) [14] to every patient to test glucose monitoring satisfaction. In addition, patient-reported satisfaction with the Medisafe Fit Smile color-coded features (MSCF) survey was collected at the final site visit [15].…”
Section: Study Proceduresmentioning
confidence: 99%
“…Alternatively, the MSCF survey includes 12 questions to measure the participant's Medisafe Fit Smile perception. A trained interviewer asked the patients to rate their experience with the system on a scale ranging from one (strongly agree) to five (strongly disagree) [15].…”
Section: Assessment Of the Patient Satisfactionmentioning
confidence: 99%
“…As a result, not only metabolic parameters and glycemic control of patients with diabetes improve, but also their diabetes management performance and satisfaction. 13,[15][16][17] The aim of this study was a system accuracy assessment and a user performance evaluation of four BGMSs with color coding of BG results.…”
Section: Introductionmentioning
confidence: 99%